Secondary Traumatization in Mental Health Workers - Bahar Yücel; Bahar Akoğlu (Psikiyatride Güncel Yaklaşımlar, 2023)
Secondary traumatic stress is an important issue that indirectly affects the mental health professionals. This research was conducted to examine the relationship between secondary traumatization, occupational burnout, and compassion fatigue among mental health workers. In line with this aim, a study was carried out using a relational screening method, employing a Semi-Structured Interview Form, Secondary Traumatic Stress Scale, Maslach Burnout Inventory, and Compassion Fatigue Scale. The study involved a total of 400 mental health professionals, comprising 298 females (74.5%) and 102 males (25.5%) aged between 24 and 65 years. The findings revealed that the avoidance, arousal, and emotional violation sub-dimensions of secondary traumatic stress significantly predicted occupational burnout, explaining 37% of the variance in the outcome variable. It was observed that the arousal and emotional violation sub-dimensions of secondary traumatic stress were not significant predictors for compassion fatigue. However, the avoidance sub-dimension significantly predicted compassion fatigue, explaining 12% of the variance in the outcome variable. The study highlighted that engaging with traumatized individuals indirectly posed a risk for professions providing mental health services due to the impact on their well-being.